Liquid Metal Switches for Environmentally Responsive Electronics. Issue 5 (5th January 2017) - Bilodeau, Raymond Adam; Zemlyanov, Dmitry Y.; Kramer, Rebecca K.
Abstract : Liquid metal droplet wetting and dewetting transitions are shown using environmental stimuli to remove, reform, and transform droplet surface oxide. A comparison is made between the speed of oxide removal using NaOH and HCl, with NaOH proving to be significantly faster. The findings are applied to demonstrate a liquid metal switch controlled through purely environmental stimuli.